Low pressure liquid pipelines in the North Slope, Greater Prudhoe Bay, Alaska : hearing before the Committee on Transportation and Infrastructure, House of Representatives, One Hundred Ninth Congress, second session, September 13, 2006. - United States. Congress. House. Committee on Transportation and Infrastructure. (Washington : U.S. G.P.O. : For sale by the Supt. of Docs., U.S. G.P.O., 2007)
"109-95." Shipping list no.: 2007-0186-P. Distributed to some depository libraries in microfiche. Includes bibliographical references. Mode of access: Internet.